PREVALENCE AND RISK FACTORS OF PEDIATRIC APPENDICITIS: A SURGICAL REVIEW AT PUMHS NAWABSHAH. : JPUMHS;2024:14:04,258-266. http://doi.org/10.46536/jpumhs/2024/14.04.586 - Naseem Mengal1, Ali Raza Brohi2, Aiman ali brohi3, Ali Faraz Brohi4, Moiz Muhammad Shaaikh5, Ayesha Sajid6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Appendicitis which describes vermiform appendix inflammation occurs as one of the most frequent surgical emergencies found among pediatric patients on a worldwide scale. OBJECTIVE: The aim of this study was to determine the prevalence and identify the risk factors associated with pediatric appendicitis in children undergoing surgical intervention at PUMHS Nawabshah. METHODOLOGY: This retrospective observational study was conducted at the Department of Pediatric Surgery, PUMHS Nawabshah, over a period of one year January 2024 to December 2024. Medical records of pediatric patients diagnosed with appendicitis and who underwent appendectomy were reviewed. Data was collected regarding patient demographics, presenting symptoms, laboratory findings, and risk factors including age, gender, nutritional status, family history, and the presence of comorbidities. The prevalence of appendicitis and its associated risk factors were analyzed using descriptive statistics. RESULTS: A total of 150 pediatric patients were included in the study, with a male-to-female ratio of 1.5:1. The prevalence of appendicitis was found to be 7.5% among pediatric patients presenting to the emergency department. The most common presenting symptoms were abdominal pain 95%, nausea/vomiting 85%, and fever 78%. Significant risk factors for appendicitis included age most common in children aged 6-12 years, male gender, and a family history of appendicitis. Nutritional status did not show a significant correlation with appendicitis occurrence. Additionally, 12% of patients had a history of recurrent abdominal pain, and 5% had a history of gastrointestinal infections. CONCLUSION: Appendicitis remains a common surgical emergency in pediatric patients. Early diagnosis and timely intervention are crucial for reducing morbidity. Male gender, age between 6-12 years, and a family history of appendicitis are significant risk factors for the condition. Further studies are recommended to evaluate the impact of nutritional status and gastrointestinal infections on the development of appendicitis in children.